Touchable Gods: Improvised Icons, Irreverent Rituals and Intimate Kinship with Deities in Rural Tamil Nadu - Arumugam, Indira (Religions of South Asia, 2021)
Village and tutelary deities have been characterized as fierce, capricious, or at least ambiguous. This article explores another facet of these polysemous divinities: their kinship with their adherents. Against the thrust of recent emphases on the gentrification of rural cults, the interventions of ritual specialists and the establishing of distance between deities and laity, these gods remain messily tactile and persist in being directly touchable. Villagers make their gods themselves with profane materials and through routine actions; enact rituals to them unmediated by priests, marked by informality and tinged with irreverence; and relate to them through instrumentalist but loving interactions. From the mundane acts and exegetic narratives through which devotees make sense of and organize their religious experiences, I materialize a local theology that articulates the nature of these gods and how they become present and active in human social worlds. Privileging co-residence, substantive congruence with, and ethical obligations between, villagers and their tutelaries, this theology presumes kinship with their gods. Taking these gods for granted, only intermittently worshipping them, and even neglecting sacrificial obligations, denotes profound intimacy between them and their devotees. Sublimity and intimacy are simultaneously part of the productive ambiguities that underpin the charisma of this sacred.